PERSONALITY MATURITY AND SUBJECTIVE WELL-BEING IN STUDENTS OF FULL-TIME AND CORRESPONDENCE FORMS OF STUDYING IN THE UNIVERSITY - Гімаєва, Юлія Азгатівна; Малофейкіна, Катерина Олексіївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
The article contains the research of connections between personality maturity and subjective wellbeing in full-time and correspondence course psychology students. The concept of personality maturity is considered in terms of O.S.Shteppe’s and Yu.Z.Hilbukh’s approaches, the concept of subjective well-being is considered in terms of E. Diener’s hedonistic approach. For empirical study there were used such methods as Personality Maturity Questionnaire Yu.Z. Hilbukh, Personality Maturity Questionnaire O.S.Shteppe , Subjec tive Well-being Scale A. Perrudet-Badoux in V.N.Sokolova adaptation, Satisfaction with Life Scale E. Diener in D.O.Leontiev adaptation, Subjective Happiness Scale S. Lyubomirsky. The subjects of the research were second year students since this period can be considered the most stable of whole studying time. It’s revealed that the most psychology students have got acceptable level of personality maturity by Yu.Z.Hilbukh that is very high, high or satisfactory level. According to O.S.Shteppe the most of them have got required level of personality maturity. Students feel subjective well-being on emotional and cognitive level by average measure, they feel happy with their life by higher than average measure. Personality maturity in general is signifiantly correlates with subjective well-being in the emotional aspect and satisfaction with life as cognitive aspect of subjective well-being in students of both forms of studying. Also the tendency to form connection between personality maturity and feeling of happiness is revealed in full-time students. Correlations between com ponents of personality maturity and subjective well-being were obtained for full-time and correspondence course students separately. In full-time student’s different aspects of subjective well-being are more wildly connected with such components of personality maturity as motivation of achievement, self-acceptance and life philosophy.In correspondence course students, aspects of subjective well-being are to more extent connected with components of personality maturity as contactability, tolerance and synergy. It can have argued that full-time students to feel emotionally comfortable need to have dispositions which regulate relations with themselves, but correspondence course students need to have dispositions which are demanded in communication and building ofrelationships.